2018
DOI: 10.3389/fevo.2018.00097
|View full text |Cite
|
Sign up to set email alerts
|

“More Than Meets the Eye”: Cryptic Diversity and Contrasting Patterns of Host-Specificity in Feather Mites Inhabiting Seabirds

Abstract: Feather mites are useful models for studying speciation due to their high diversity and strong degree of host specialization. However, studies to date have focused on the evolution of higher-level mite taxa while much hidden diversity likely occurs at the level of host genera and species. In this study, we examined the diversity and evolution of feather mites infesting six sympatric seabird species from six genera, breeding in the Cape Verde archipelago. We report 32 feather mite morphospecies categorized into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 79 publications
(98 reference statements)
2
14
0
Order By: Relevance
“…Unfortunately, non-phoretic females of S. acarorum were not available from different geographic locations to test whether their morphological pattern mirrors that of their phoretic conspecifics. Similar host-associated adaptive pressures have also been reported for other ectosymbionts such as feather mites (Stefan et al 2018 ).…”
Section: Discussionsupporting
confidence: 77%
“…Unfortunately, non-phoretic females of S. acarorum were not available from different geographic locations to test whether their morphological pattern mirrors that of their phoretic conspecifics. Similar host-associated adaptive pressures have also been reported for other ectosymbionts such as feather mites (Stefan et al 2018 ).…”
Section: Discussionsupporting
confidence: 77%
“…Indeed, a relationship between genetic divergence and host specificity has also been reported from other parasites, such as the honey bee parasite Varroa (Beaurepaire et al, 2015) and Macrocheles species that are associated with Nicrophorus beetles (Knee, 2017). Genetic clustering driven by host adaptation is also found in feather mites that are phoretic on seabirds (Stefan et al, 2018). Host specificity is often seen as a species-level trait.…”
Section: Drivers Of Speciationmentioning
confidence: 82%
“…Commonly harvested birds such as Common Eiders and murres have experienced pathogenicity, mortality, and even annual colony collapse due to increased parasitism (Gaston et al, 2002;Gaston and Elliott, 2013;Kristjánsson et al, 2016;Lovvorn et al, 2009). Anthropogenic activities such as overfishing and oceanic pollution are also evolving factors contributing to reduced health in seabirds (Braune et al, 2006;Sydeman et al, 2017). The long-term impacts of these changes can contribute to increased, additive mortality caused by parasites in seabird colonies.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Stefan et al (2015) determined that a single bird can play host to multiple species of mites (Microspalax brevipes and Zachvatkinia ovate) due to resource partitioning and spatial segregation among the species. Indeed, a more recent study found up to eight different mite species exploiting Cape Verde Shearwaters (Calonectris edwardsii) and Bulwer's Petrels (Bulweria bulwerii; Stefan et al, 2018). However, the effects of mites on wild seabirds are largely unknown.…”
Section: Ticksmentioning
confidence: 99%
See 1 more Smart Citation